O processo de demarcação dos terrenos de marinha : uma releitura em conformidade com a constituição de 1988 - Dantas, Fernando Luis Lopes (2015)
Tide lands are owned by the Union, pursuant to art. 20, VII, of the Constitution of 1988. Despite this reference, the Constitution did not try to present the characteristic features of these assets, nor specifically ruled on its demarcation process, and these issues governed by constitutional legislation, in particular by Decree law No. 9760, issued in 1946. Since then, Brazil has owned four other beyond 1988. With this Constitution, rather than bring together the state of democratic experience, there was the so-called phenomenon of constitutionalization of Administrative Law. A new behavioral paradigm was established for Public Administration, which has been governed closely by constitutional rules, which elected the process as the primary form of performance of government agencies. The constituent power also took care to define the elements considered essential to the development of a fair trial, that beyond simple compliance to certain procedural specific regulations, is based on the firm commitment to carry out the fundamental rights of individuals. Given the new state model designed by the 1988 Constitution, imposed the need to promote a review of the various specific regulations on State processes in order to conform them to existing constitutional requirements. And this opportunity, especially the temporal distance from when edited Decree-Law No. 9,760 / 1946, as well as the anti-democratic context in the midst of which was issued, the review of the normative discipline of demarcation activity of tide lands appeared as urgent measure. Rereading promoted this work was guided by axiological vector announced from the constitutional preamble: the realization of justice and fundamental rights of individuals, in particular where the right to property and the procedural. Although that lacks Decree Law update, this measure does not seem essential, since their harmonization with the constitutional provisions and the provisions of Law No. 9,784 / 1999, which can be performed only from hermeneutical resources, which must honor the supremacy and the normative force of the Constitution. It follows, first of all, the requirement that the demarcation activity is promoted without remission or emptying of the procedural formula. Your result should pinpoint the location of tide lands with strict attention to the essential elements that make up the legal concept of this institute: the spatial framework, which is the line is the average of high tides, the temporal reference to the year 1831 and finally the systematic calculation of those averages. Should not interest the Union, as one of the entities that embodies the state, as its state even one square centimeter beyond what the Constitution gave it, as this would represent a breach of the duty of protection to which it is bound, and that overlaps any secondary interest, notably revenue collection. The due process of demarcation, which meets all requirements of legal and constitutional framework, is therefore the only instrument able to promote necessary and possible harmonization between the interests of the Union and individuals in general.